(untitled) (Studia theodisca, 2025)
This article examines the representation of femininity and masculinity in Friedrich Hölderlin’s Hyperion oder der Eremit in Griechenland. The findings are related on the one hand to the contemporary gender debate around 1800 and on the other to the narrative structure of the novel itself. Via the female main character Diotima, it is possible to show the philosophical ‘enrichment’ that is characteristic of the novel. As a consequence, Diotima selectively transcends the boundaries of her gender. Applying a holistic approach that considers the underlying research results of men’s studies, the article goes on to focus on Hyperion and Alabanda. In doing so, the article examines the three main types of masculinity around 1800 (civil servant, warrior, poet) and how they contribute to the protagonist’s development.